Multilateral Versus Unilateral Sanctions Reconsidered: A Test Using New Data - Bapat, Navin A.; Clifton Morgan, T. (International studies quarterly, 2009)
Policymakers frequently argue that multilateral sanctions are more likely to induce a target state to alter its behavior than are unilateral sanctions. Repeated empirical studies using the Familiar Haufbauer, Schott, and Elliot data set demonstrate that unilateral sanctions "work" more often than multilateral sanctions, however. In this study, we subject three theoretical explanations for this counterintuitive finding to additional empirical testing utilizing the new Threat and Imposition of Economic Sanctions (TIES) data. Somewhat surprisingly, the analyses using these new data support the intuition of policymakers; that is, multilateral sanctions do appear to work more frequently than do unilateral sanctions. Our results do support one theoretical arguments, based on spatial models, that we test. This explanation holds that whether multilateral or unilateral sanctions are more effective depends on the number of issues at stake and on whether an international institution is involved. Our analyses provide support for these hypotheses.